Schreiben im Ersten Weltkrieg: französische Briefe und Tagebücher wenig geübter Schreiber aus der deutsch-französischen Grenzregion - Sowada, Lena (Beihefte zur Zeitschrift für romanische Philologie, 2021)
"What shape does written language usage take in the diaries and letters of people with little routine or experience in writing? This volume looks at the geopolitical and historical context, the acquisition of written language and individual writing socialisation in order to examine this kind of writing on various linguistic levels as the expression of a heterogenous range of writing skills and different written language usage norms."--Publisher's website